Enhanced fixation of dissolved inorganic carbon by algal-bacterial aerobic granular sludge during treatment of low-organic-content wastewater. (June 2023) - Xu, Jing; Yuan, Tian; Wang, Lanting; Zhang, Chi; Lei, Zhongfang; Shimizu, Kazuya; Zhang, Zhenya
Graphical abstract: Highlights: The optimal inorganic carbon (IC) content for its fixation by A-BAGS was explored. Effects on nitrogen removal and changes in microbial community were analyzed. 1.4-fold higher biomass yield and 1.5-fold higher EPS of A-BAGS at optimal condition. Good granular stability and nitrification efficiency were kept at optimal condition. Enriched Nitrospirae and Bacillariophyceae contributed to nitrogen and carbon removal. Abstract: The microalgae-based wastewater treatment technologies are believed to contribute to carbon neutrality. This study investigated the inorganic carbon fixation performance in the algal-bacterial aerobic granular sludge (A-BAGS) process under cultivation at different concentrations of organic carbon (OC) and inorganic carbon (IC). The results indicated that A-BAGS in treating wastewater containing organics of 77 mg-C/L contributed little to the fixation of inorganic carbon, while the highest inorganic carbon removal efficiency of 50 % was achieved at the influent IC of 100 mg/L and OC of 7 mg/L. This high IC condition contributed to enhanced biomass growth rate and enhanced extracellular polymeric substances, while it did not affect the granular stability and nitrification efficiency. The microbial diversity was also largely enhanced. The results demonstrated the great potential of A-BAGS for simultaneous resource recovery in wastewater and inorganic carbon fixation, while operation conditions need to be further optimized.